Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Section 12.2 Answers

  • Page ID
    30077
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    1. \(u(x,t)=\frac{4}{3\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{(2n-1)^{3}}\sin 3(2n-1)\pi t\sin (2n-1)\pi x\)

    2. \(u(x,t)=\frac{8}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\cos 3(2n-1)\pi t\sin (2n-1)\pi x\)

    3. \(u(x,t)=-\frac{4}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(1+(-1)^{n}2)}{n^{3}}\cos n\sqrt{7}\pi t\sin n\pi x\)

    4. \(u(x,t)=\frac{8}{3\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\sin 3(2n-1)\pi t\sin (2n-1)\pi x\)

    5. \(u(x,t)=-\frac{4}{\sqrt{7}\pi ^{4}} \sum_{n=1}^{\infty}\frac{(1+(-1)^{n}2)}{n^{4}}\sin n\sqrt{7}\pi t\sin n\pi x\)

    6. \(u(x,t)=\frac{324}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{3}}\cos\frac{8n\pi t}{3}\sin\frac{n\pi x}{3}\)

    7. \(u(x,t)=\frac{96}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\cos 2(2n-1)\pi t\sin (2n-1)\pi x\)

    8. \(u(x,t)=\frac{243}{2\pi ^{4}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{4}}\sin\frac{8n\pi t}{3}\sin\frac{n\pi x}{3}\)

    9. \(u(x,t)=\frac{48}{\pi ^{6}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{6}}\sin 2(2n-1)\pi t\sin (2n-1)\pi x\)

    10. \(u(x,t)=\frac{\pi }{2}\cos\sqrt{5}t\sin x-\frac{16}{\pi} \sum_{n=1}^{\infty}\frac{n}{(4n^{2}-1)^{2}}\cos 2n\sqrt{5}t\sin 2nx\)

    11. \(u(x,t)=-\frac{240}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{5}}\cos n\pi t\sin n\pi x\)

    12. \(u(x,t)=\frac{\pi }{2\sqrt{5}}\sin\sqrt{5}t\sin x-\frac{8}{pi\sqrt{5}} \sum_{n=1}^{\infty}\frac{1}{(4n^{2}-1)^{2}}\sin 2n\sqrt{5}t\sin 2nx\)

    13. \(u(x,t)=-\frac{240}{\pi ^{6}} \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{6}}\sin n\pi t\sin n\pi x\)

    14. \(u(x,t)=-\frac{720}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{5}}\cos 2n\pi t\sin n\pi x\)

    15. \(u(x,t)=-\frac{240}{\pi ^{6}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{6}}\sin 3n\pi t\sin n\pi x\)

    18. \(u(x,t)=-\frac{128}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{3}}\cos\frac{3(2n-1)\pi t}{4}\cos \frac{(2n-1)\pi x}{4}\)

    19. \(u(x,t)=-\frac{64}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\cos (2n-1)\pi t\cos\frac{(2n-1)\pi x}{2}\)

    20. \(u(x,t)=-\frac{512}{3\pi ^{4}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{4}}\sin\frac{3(2n-1)\pi t}{4}\cos\frac{(2n-1)\pi x}{4}\)

    21. \(u(x,t)=-\frac{64}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\sin (2n-1)\pi t\cos\frac{(2n-1)\pi x}{2}\)

    22. \(u(x,t)=\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}3+\frac{4}{(2n-1)\pi}\right]\cos\frac{(2n-1)\sqrt{5}\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    23. \(u(x,t)=-96\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}+\frac{2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\sqrt{3} t}{2}\cos\frac{(2n-1) x}{2}\)

    24. \(u(x,t)=\frac{192}{\pi ^{4}\sqrt{5}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}3+\frac{4}{(2n-1)\pi}\right]\sin\frac{(2n-1)\sqrt{5}\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    25. \(u(x,t)=-\frac{192}{\sqrt{3}}\sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{2}{(2n-1)\pi}\right]\sin\frac{(2n-1)\sqrt{3}t}{2}\sin\frac{(2n-1)x}{2}\)

    26. \(u(x,t)=-\frac{384}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+\frac{(-1)^{n}4}{(2n-1)\pi}\right]\cos\frac{3(2n-1)\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    27. \(u(x,t)=\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[(-1)^{n}5+\frac{8}{(2n-1)\pi}\right]\cos\frac{(2n-1)\sqrt{7}\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    28. \(u(x,t)=-\frac{768}{3\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\left[1+\frac{(-1)^{n}4}{(2n-1)\pi}\right]\sin\frac{3(2n-1)\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    29. \(u(x,t)=\frac{192}{\pi ^{4}\sqrt{7}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}5+\frac{8}{(2n-1)\pi}\right]\sin\frac{(2n-1)\sqrt{7}\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    30. \(u(x,t)=-\frac{768}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+\frac{(-1)^{n}2}{(2n-1)\pi}\right]\cos\frac{(2n-1)\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    31. \(u(x,t)=-\frac{1536}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\left[1+\frac{(-1)^{n}2}{(2n-1)\pi}\right]\sin\frac{(2n-1)\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    32. \(u(x,t)=\frac{1}{2}\left[C_{Mf}(x+at)+C_{Mf}(x-at)\right]+\frac{1}{2a} \int_{x-at} ^{x+at} C_{Mg}(\tau )d\tau \)

    35. \(u(x,t)=\frac{32}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\cos 4(2n-1)t\sin\frac{(2n-1)x}{2}\)

    36. \(u(x,t)=-\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[ 1+(-1)^{n}\frac{4}{(2n-1)\pi}\right]\cos\frac{3(2n-1)\pi t}{2}\sin\frac{(2n-1)\pi x}{2}\)

    37. \(u(x,t)=\frac{8}{\pi} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\sin 4(2n-1)t\sin\frac{(2n-1)x}{2}\)

    38. \(u(x,t)=-\frac{64}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[1+(-1)^{n}\frac{4}{(2n-1)\pi}\right]\sin\frac{3(2n-1)\pi t}{2}\sin\frac{(2n-1)\pi x}{2}\)

    39. \(u(x,t)=\frac{96}{\pi ^{3}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{3}}\left[1+(-1)^{n}\frac{2}{(2n-1)\pi}\right]\cos\frac{3(2n-1)\pi t}{2}\sin\frac{(2n-1)\pi x}{2}\)

    40. \(u(x,t)=\frac{192}{\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{4}}\cos\frac{(2n-1)\sqrt{3}t}{2}\sin\frac{(2n-1)x}{2}\)

    41. \(u(x,t)=\frac{64}{\pi ^{4}} \sum_{n=1}^{\infty} \frac{1}{(2n-1)^{4}}\left[1+(-1)^{n}\frac{2}{(2n-1)\pi}\right]\sin\frac{3(2n-1)\pi t}{2}\sin\frac{(2n-1)\pi x}{2}\)

    42. \(u(x,t)=\frac{384}{\sqrt{3}\pi} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{(2n-1)^{5}}\sin\frac{(2n-1)\sqrt{3}t}{2}\sin\frac{(2n-1)x}{2}\)

    43. \(u(x,t)=\frac{1536}{\pi^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\cos\frac{(2n-1)\sqrt{5}\pi t}{2}\sin\frac{(2n-1)\pi x}{2}\)

    44. \(u(x,t)=\frac{384}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\left[(-1)^{n}+\frac{4}{(2n-1)\pi}\right]\cos (2n-1)\pi t\sin\frac{(2n-1)\pi x}{2}\)

    45. \(u(x,t)=\frac{3072}{\sqrt{5}\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\left[(-1)^{n}+\frac{3}{(2n-1)\pi}\right]\sin\frac{(2n-1)\sqrt{5}\pi t}{2}\sin\frac{(2n-1)\pi x}{2}\)

    46. \(u(x,t)=\frac{384}{\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\left[(-1)^{n}+\frac{4}{(2n-1)\pi}\right]\sin (2n-1)\pi t\sin \frac{(2n-1)\pi x}{2}\)

    47. \(u(x,t)=\frac{1}{2}[S_{Mf}(x+at)+S_{Mf}(x-at)]+\frac{1}{2a} \int_{x-at} ^{x+at} S_{Mg}(\tau )d\tau \)

    50. \(u(x,t)=4-\frac{768}{\pi^{4}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{4}}\cos\frac{\sqrt{5}(2n-1)\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    51. \(u(x,t)=4t-\frac{1536}{\sqrt{5}\pi ^{5}} \sum_{n=1}^{\infty}\frac{1}{(2n-1)^{5}}\sin\frac{\sqrt{5}(2n-1)\pi t}{2}\cos\frac{(2n-1)\pi x}{2}\)

    52. \(u(x,t)=-\frac{2\pi ^{4}}{5}-48 \sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{4}}\cos 2nt\cos nx\)

    53. \(u(x,t)=-\frac{7}{5}-\frac{144}{\pi ^{4}} \sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{4}}\cos n\sqrt{7}\pi t\cos n\pi x\)

    54. \(u(x,t)=-\frac{2\pi ^{4}t}{5}-24\sum_{n=1}^{\infty}\frac{1+(-1)^{n}2}{n^{5}}\sin 2nt\cos nx\)

    55. \(u(x,t)=-\frac{7t}{5}-\frac{144}{\pi ^{5}\sqrt{7}}\sum_{n=1}^{\infty}\frac{(-1)^{n}}{n^{5}}\sin n\sqrt{7}\pi t\cos n\pi x\)

    56. \(u(x,t)=\frac{\pi ^{4}}{30}-3\sum_{n=1}^{\infty}\frac{1}{n^{4}}\cos 8nt\cos 2nx\)

    57. \(u(x,t)=\frac{3}{5}-\frac{48}{\pi ^{4}}\sum_{n=1}^{\infty}\frac{2+(-1)^{n}}{n^{4}}\cos n\pi t\cos n\pi x\)

    58. \(u(x,t)=\frac{\pi ^{4}t}{30}-\frac{3}{8}\sum_{n=1}^{\infty}\frac{1}{n^{5}}\sin 8nt\cos 2nx\)

    59. \(u(x,t)=\frac{3t}{5}-\frac{48}{\pi ^{5}}\sum_{n=1}^{\infty}\frac{2+(-1)^{n}}{n^{5}}\sin n\pi t\cos n\pi x\)

    60. \(u(x,t)=\frac{1}{2}\left[ C_{f}(x+at)+C_{f}(x-at)\right] +\frac{1}{2a} \int _{x-at}^{x+at} C_{g}(\tau )d\tau \)

    63. c. \(u(x,t)=\frac{f(x+at)+f(x-at)}{2}+\frac{1}{2}\int_{x-at}^{x+at} g(u)du\)

    64. \(u(x,t)=x(1+4at\)

    65. \(u(x,t)=x^{2}+a^{2}t^{2}+t\)

    66. \(u(x,t)=\sin (x+at)\)

    67. \(u(x,t)=x^{3}+6tx^{2}+3a^{2}t^{2}x+2a^{2}t^{3}\)

    68. \(u(x,t)=x\sin x\cos at+at\cos x\sin at+\frac{\sin x\sin at}{a}\)